[I+E]² Colección Caja de Burgos. - Caja de Burgos, Burgos (Burgos : CAB (Centro de Arte Caja de Burgos) Burgos, 2011)
van Eeden, Marcel ; Perejaume ; Resbier, Eduard ; Maldonado, José ; Kondratiuk, Gabriel ; Guijarro, José Maria ; Moro, Teresa ; Molo ; Pardo, Jorge ; Laarman, Joris ; Criado, Rufo ; Huete, Sara ; Leal, Miki ; Calleja, Javier ; Baker, Bridget ; Rubio, Rosa ; Rey, Alberto ; Olivier, Jacco ; Gruber, Eduardo ; Oschatz, Julia ; Assig, Martin ; Bermejo, Nati ; Pereira, Pamen ; Giezendanner, Ingo ; Arce, Javier ; Goiris, Geert ; Navarro, Iván ; Arrechea, Alex ; Vilches, Manuel ; Rousse, Georges ; Eskinja, Igor ; Romeu, Concha ; The Royal Art Lodge
Engels en Spaans
Exhibition. [I+E]² Colección Caja de Burgos. CAB (Centro de Arte Caja de Burgos) Burgos. 2011-01-28. 2011-09-11
boek